Analisis Nilai Kecepatan Tangki Riak dengan Laboratorium Virtual PhET dan Riil di Laboratorium Fisika - Purwanti, Popi; Saraswati, Dandan Luhur (Universitas Halu Oleo, 2020)
This research is useful to develop the potential in physics education students to use virtual practicum with PhET Simulation and practicum rill. PhET Simulation is a series of interactive virtual practical simulations. In the implementation of practicum rill by using a kit set of ripple tank tools. to determine the speed value on the ripple tank see the wavelength that occurs at each frequency. To determine the speed value on the ripple tank see the wavelength that occurs at each frequency. The results of the analysis of the speed value in the ripple tank using PhET Simulation were obtained by V=(0.0832 Â± 0.208384) m/s and the result of the speed value on the ripple tangka using kit practicum tool obtained by V= |0.0183 Â± 0.367420 |Â m/s. It is easier to practice using a virtual laboratory with the help of phet simulation application is very effective for analysis of physics experiments.